1992
DOI: 10.1002/aja.1001930410
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of engrailed‐like proteins in the chick embryo

Abstract: The protein products of both of the identified chick engrailed-like (En) genes, chick En-1 and chick En-2, are localized in cells of the developing brain, mandibular arch, spinal cord, dermatome, and ventral limb bud ectoderm, as demonstrated by labeling with the polyclonal antiserum cuEnhb-1 developed by Davis et al. (Development 111:281-298, 1991). A subpopulation of cephalic neural crest cells is also En-protein-positive. The monoclonal antibody 409 recognizes the chick En-2 gene product exclusively (Patel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 85 publications
5
45
0
Order By: Relevance
“…In vertebrates, by contrast, En expression occurs regionally, in a fashion that is difficult to reconcile with the segmental model (Patel et al, 1989). En gene expression in vertebrates has a complex and changing pattern during embryonic and postembryonic morphogenesis in mesodermal and ectodermally derived tissues (Davis et al, 1988(Davis et al, , 1991Gardner et al, 1989;Hatta et al, 1991;Gardner and Barald, 1992). Consistent with a broad function, En-1 knockout mice have multiple developmental defects, including loss of much of the cerebellum and colliculi, truncation and duplication of digits, and defects of sternum and ribs (Wurst et al, 1994).…”
Section: Pathway Formation and Differential Cell Adhesionmentioning
confidence: 94%
“…In vertebrates, by contrast, En expression occurs regionally, in a fashion that is difficult to reconcile with the segmental model (Patel et al, 1989). En gene expression in vertebrates has a complex and changing pattern during embryonic and postembryonic morphogenesis in mesodermal and ectodermally derived tissues (Davis et al, 1988(Davis et al, , 1991Gardner et al, 1989;Hatta et al, 1991;Gardner and Barald, 1992). Consistent with a broad function, En-1 knockout mice have multiple developmental defects, including loss of much of the cerebellum and colliculi, truncation and duplication of digits, and defects of sternum and ribs (Wurst et al, 1994).…”
Section: Pathway Formation and Differential Cell Adhesionmentioning
confidence: 94%
“…Force et al (1999) showed that this might be the case for the En1 genes in zebrafish. In mouse and chicken, En1 is expressed in the developing pectoral appendage bud and in specific neurons of the hindbrain and spinal cord (Joyner and Martin 1987;Davis et al 1991;Gardner and Barald 1992). In zebrafish, however, one of the paralogs is expressed in the pectoral appendage bud, while the second paralog is expressed in the hindbrain/spinal cord neurons (Force et al 1999).…”
Section: Redundancy or Functional Divergence?mentioning
confidence: 99%
“…Force et al (1999) showed that this model might generally apply based on the En1 genes in zebrafish. In mouse and chicken, En1 is expressed in the developing pectoral appendage bud and in specific neurons of the hindbrain and spinal cord (Joyner and Martin, 1987;Davis et al, 1991;Gardner and Barald, 1992). In zebrafish, however, one of the paralogs is expressed in the pectoral appendage bud, while the second paralog is expressed in the hindbrain/spinal cord neurons (Force et al, 1999).…”
Section: The Evolutionary Consequences Of An Ancient Fish-specific Gementioning
confidence: 99%